ChemInform Abstract: Oxygen Switch in Visible‐Light Photoredox Catalysis: Radical Additions and Cyclizations and Unexpected C—C‐Bond Cleavage Reactions. Issue 29 (1st July 2013) - Zhu, Shaoqun; Das, Arindam; Bui, Lan; Zhou, Hanjun; Curran, Dennis P.; Rueping, Magnus
Abstract: N, N‐Dimethylanilines react with benzylidene malononitriles to afford γ‐amino nitriles [cf.